Slowo i cialo : powiesc z lat 201-203 - Parnicki, Teodor (Warszawa : Instytut Wydawniczy Pax, 1981)
An historical novel of Rome taking place in the early part of the 3rd century, during the reign of Septimius.
Keywords: Rome -- History -- Lucius Septimius Severus, 193-211 -- Fiction